Sierpień w hrabstwie Osage – analiza filmu z uwzględnieniem kategorii skryptu życiowego - Piasecka, Paulina (Edukacyjna Analiza Transakcyjna, 2014)
The article presents an attempt at the analysis of a movie entitled August: Osage County from the perspective of one of the most important Transacional Analysis categories, life script. This movie presents the story of a dysfunctional family from Missouri, in which parents’ destructive patterns of behavior destroy the lives of the next generation.